Real time modeling and control of a wind farm connected to a multi-bus network under faulty conditions. (October 2019) - Benaama, Kamel; Khiat, Mounir; Barkat, Said
Abstract: This paper describes the detailed modeling and simulation of an aerogenerators system based on DFIG using RT-LAB simulator. A stator flux oriented vector is applied to decouple the control of active and reactive powers generated by the DFIG, and other controllers are needed to keep the DC-link voltage and grid currents at desired values. In order to adjust appropriately the pitch angle and keep the wind power at rated value, a pitch control and MPPT are involved. The model of the studied was developed first in the MATLAB ®, then, it was rebuilt on RT-LAB to test its performance. Simulation results validate the capability of the platform to achieve rapid simulation of complex power systems. At the end, the details of the simulation results are presented, discussed, and concluded. Highlights: Detailed understanding of both modeling and control of DFIG based aerogenerators integrated in an HVAC is presented. Comprehensive of real-time simulation steps of a complex power system are presented. RT-LAB based real-time simulations of a wind farm connected to a large power system in faulty conditions are illustrated and discussed.